Effect of silver nanoparticles in a hydroxyapatite coating applied by atmospheric plasma spray - Orozco Carmona, V.; Martínez Pérez, C.; de Lima, Renata; Fraceto, Leonardo Fernandes [UNESP]; Romero García, J.; Ledezma Pérez, A.; Marke, Swen; Rodríguez González, C.; Macías, Abel Hurtado; Martínez-Villafañe, A. (My University, 2014)
In this study, 0.5, 1, 3, and 5 % nano-silver containing hydroxyapatite coatings (nAg-HA) on a Ti6Al4V substrate were developed by atmospheric plasma spray (APS), and their antibacterial efficiency was evaluated in the following bacterial strains: Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The optimal operating parameters for the coatings application were determined by online diagnostic of thermal HVOF- and plasma spraying processes. Scanning electron microscopy (SEM) showed that both micro and nano-silver (Ag) particles were distributed on the coating surface. The antibacterial efficiency was studied according to the JIS Z2801:2000 standard Antimicrobial products-Test for antimicrobial activity and efficacy. The results show that the antibacterial efficiency of a 1 % nAg-HA coating against Escherichia coli, Pseudomonas aeruginosa, and Pseudomonas aeruginosa strains was above 99 % antibacterial rate. Silver ion release tests show that the coatings did not deliver the silver ions in the phosphate buffered saline solution, which generate good cytotoxic properties. The antibacterial mechanisms observed in the coatings are based in the combination of the two following theories proposed by Cao: 1) Disruption of transmembrane proton electrochemical gradient, and 2) bacterial charging process. The electrochemical test in SBF solution at 25 and 37 °C showed an icorr higher than 25.00E-6 A/cm2, which justified the good antibacterial properties. The nAg-HA coatings developed presented excellent bond strength (35 MPa in average), nano-mechanical properties, and the failure mode was identified as adhesion-cohesion. This study opens perspectives for the development of in-vivo tests of the nAg-HA coatings applied by APS; research in an alternative method to enhance the nano-particles dispersion into the HA matrix; and finally, the study suggests further research to determine which of the two mechanisms proposed by Cao presents the major effect in the antibacterial rate.
Keywords: Antibacterial test; Atmospheric plasma spray; Cytotoxic test; Electrochemical test; Hydroxyapatite coating; Silver nano particles